Analysis of the Competency Relationship of a Project Manager Based on Three Aspects, namely "Perception of Project Manager Competence on the Success of the Mandai Simpang Lima Under Pass Road Construction Project" - Rizki Ayu Saraswati (UNDERPASS Journal of Civil Engineering, Applied Sciences, and Technology, 2018)
A project is said to be successful if the project is able to be completed at a competitive cost, can be completed on time or even faster than the scheduled time, and with the achievement of quality. For this reason, a reliable project manager is needed, who knows what his duties are as a project leader and has the required competency requirements. The competence of a project manager can be measured in three ways, namely knowledge or knowledge, skills or expertise and attitude or attitude. The results of the Pearson Correlation analysis show that of the eleven independent variables, only six are correlated with project success, including Communication and Scope Management, Human Resource Management, Leadership and Project Management, Professionalism and Management Issues, Responsibilities, Dreams and Priorities. Simultaneously these six independent variables have a significant influence on the project success variable. This is evidenced from the results of the F test or multiple correlation test which shows that the value of Sig. 0.032 < 0.050. So it can be said that the competence of the project manager has a significant influence on the success of the project. The influence of a project manager's competence on the success of the project can be said to be not too large, this is evidenced in the Model Summaryb table, by looking at the Adjusted R Square value of 0.080. The six independent variables only have an effect of 8% on the variation (up and down) of project success, and for 92% it is influenced by other variables not included in this study.